If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(7x + -3) = 2x + 4 Reorder the terms: 2x(-3 + 7x) = 2x + 4 (-3 * 2x + 7x * 2x) = 2x + 4 (-6x + 14x2) = 2x + 4 Reorder the terms: -6x + 14x2 = 4 + 2x Solving -6x + 14x2 = 4 + 2x Solving for variable 'x'. Reorder the terms: -4 + -6x + -2x + 14x2 = 4 + 2x + -4 + -2x Combine like terms: -6x + -2x = -8x -4 + -8x + 14x2 = 4 + 2x + -4 + -2x Reorder the terms: -4 + -8x + 14x2 = 4 + -4 + 2x + -2x Combine like terms: 4 + -4 = 0 -4 + -8x + 14x2 = 0 + 2x + -2x -4 + -8x + 14x2 = 2x + -2x Combine like terms: 2x + -2x = 0 -4 + -8x + 14x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + -4x + 7x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -4x + 7x2)' equal to zero and attempt to solve: Simplifying -2 + -4x + 7x2 = 0 Solving -2 + -4x + 7x2 = 0 Begin completing the square. Divide all terms by 7 the coefficient of the squared term: Divide each side by '7'. -0.2857142857 + -0.5714285714x + x2 = 0 Move the constant term to the right: Add '0.2857142857' to each side of the equation. -0.2857142857 + -0.5714285714x + 0.2857142857 + x2 = 0 + 0.2857142857 Reorder the terms: -0.2857142857 + 0.2857142857 + -0.5714285714x + x2 = 0 + 0.2857142857 Combine like terms: -0.2857142857 + 0.2857142857 = 0.0000000000 0.0000000000 + -0.5714285714x + x2 = 0 + 0.2857142857 -0.5714285714x + x2 = 0 + 0.2857142857 Combine like terms: 0 + 0.2857142857 = 0.2857142857 -0.5714285714x + x2 = 0.2857142857 The x term is -0.5714285714x. Take half its coefficient (-0.2857142857). Square it (0.08163265305) and add it to both sides. Add '0.08163265305' to each side of the equation. -0.5714285714x + 0.08163265305 + x2 = 0.2857142857 + 0.08163265305 Reorder the terms: 0.08163265305 + -0.5714285714x + x2 = 0.2857142857 + 0.08163265305 Combine like terms: 0.2857142857 + 0.08163265305 = 0.36734693875 0.08163265305 + -0.5714285714x + x2 = 0.36734693875 Factor a perfect square on the left side: (x + -0.2857142857)(x + -0.2857142857) = 0.36734693875 Calculate the square root of the right side: 0.606091527 Break this problem into two subproblems by setting (x + -0.2857142857) equal to 0.606091527 and -0.606091527.Subproblem 1
x + -0.2857142857 = 0.606091527 Simplifying x + -0.2857142857 = 0.606091527 Reorder the terms: -0.2857142857 + x = 0.606091527 Solving -0.2857142857 + x = 0.606091527 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2857142857' to each side of the equation. -0.2857142857 + 0.2857142857 + x = 0.606091527 + 0.2857142857 Combine like terms: -0.2857142857 + 0.2857142857 = 0.0000000000 0.0000000000 + x = 0.606091527 + 0.2857142857 x = 0.606091527 + 0.2857142857 Combine like terms: 0.606091527 + 0.2857142857 = 0.8918058127 x = 0.8918058127 Simplifying x = 0.8918058127Subproblem 2
x + -0.2857142857 = -0.606091527 Simplifying x + -0.2857142857 = -0.606091527 Reorder the terms: -0.2857142857 + x = -0.606091527 Solving -0.2857142857 + x = -0.606091527 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2857142857' to each side of the equation. -0.2857142857 + 0.2857142857 + x = -0.606091527 + 0.2857142857 Combine like terms: -0.2857142857 + 0.2857142857 = 0.0000000000 0.0000000000 + x = -0.606091527 + 0.2857142857 x = -0.606091527 + 0.2857142857 Combine like terms: -0.606091527 + 0.2857142857 = -0.3203772413 x = -0.3203772413 Simplifying x = -0.3203772413Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.8918058127, -0.3203772413}Solution
x = {0.8918058127, -0.3203772413}
| -7x-4=17 | | 5x+5=-3x-27 | | 24x+12=2(12x+6) | | =9a+4b+4+4a+5b+7 | | 1.4-0.04x=5.2 | | -3=-3+x+4x | | 6v^3+15v^2+5v=0 | | 2(4-x)=2 | | 21=-3(x+14) | | 0.25t+30.00=59.50 | | =2b+8b+a+6b+10 | | 8a^2-9a+1=0 | | -12x+50=-94 | | -3u+50=75 | | 2s-5=-11 | | 17-x=5 | | 5s-2=-11 | | 4x+5-8x-6=7 | | 9x-15=30 | | 6.22x+64=38.6884+8x | | -2x+2=14 | | 2.25g+2.50=9.25 | | 5x+287=2358 | | 26=6(5+a) | | =5a+6+a+5+13a | | -2x+17=-x+5-4 | | 5.5(x-4)=-.5x+14 | | 2-5s=-11 | | 71-3x=7x-21 | | 2358=287+5x | | (2x-1)(3x+4)=2 | | 59-7x=2x+18 |